Identification and expression of Fasciola gigantica thioredoxin - Narin Changklungmoa (2018)
In the present study, a cDNA encoding Trx from F. gigantica (FgTrx) was cloned by polymerase chain reaction (PCR). The sequence of FgTrx, analyzed by BLAST, SignalP, and ClustralW programs, showed 315 bp of an open reading frame (ORF), 12 bp 5'UTR, 78 bp 3'UTR, and the putative FgTrx peptide comprising of 104 amino acids, with a molecular weight of 11.68 kDa, with the active site containing five amino acids (tryptophan, cysteine, glycine, proline, cysteine) with a conserved dithiol motif from the two cysteines, and pI 5.86. The peptide had no signal sequence; hence, it was not a secreted protein. The recombinant FgTrx was expressed in Escherichia coli BL21 (DE3) and used for production for a polyclonal antibody in rabbits (anti-rFgTrx). The FgTrx protein expression, estimated by indirect ELISA using the rabbit anti-rFgTrx as probe, showed high levels in eggs, 2- and 4-week-old juveniles, and adult parasite. In a functional test, the rFgTrx exhibited specific activity that could be suppressed by an inhibitor (PX12). When tested by immunoblotting and immunohistochemistry, rabbit anti-rFgTrx reacted with natural FgTrx at a molecular weight of 11.68 kDa from eggs, metacercariae, NEJ, 2- and 4-week-old juveniles, and adult F. gigantica. The FgTrx protein was distributed at high levels in the tegument of 2- and 4-week-old juveniles, and the tegument, parenchyma, eggs, and reproductive organs of adult parasites. FgTrx may be one of the major factors acting against oxidative stresses that can damage the parasite; hence, it could be considered as a novel vaccine or drug target. © 2014 Springer-Verlag.